Participatory action research as praxis: Developing scientifically literate students through inquiry-based science instruction and guided reading - Rhonda L Nixon (Networks: An Online Journal for Teacher Research, 2012)
Two grade six teachers, Sara and Colleen, and myself, Rhonda, a literacy coach, engaged in critical participatory action research (Kemmis & McTaggart, 2005) to inquire into our grade six students’ declining performance in science. Our research questions were: How does guided reading impact students’ reading practices in science? How does our critical or praxis-based approach to professional learning impact our students as collaborative learners? At the time when we became a teacher researcher team, Sara had taught grade six for a few years at the school. Colleen was an experienced grade six teacher coming from another school, and I was an Elementary Language Arts Consultant leaving the district office to be the new assistant principal and literacy coach in the school. As a literacy coach, I shared planning, teaching and assessment responsibilities for science and English language arts with Sara and Colleen. I was also a part-time doctoral student in language and literacy, so Sara and Colleen asked me to share what I was learning in my studies by meeting regularly to read and talk about research.